Note on the diet of the Long-whiskered Owlet, Xenoglaux loweryi from Yambrasbamba, Amazonas - Alarcón, Alejandro (2016)
We present results of an analysis of faecal samples from the long whiskered owlet (Xenoglaux loweryi), a species endemic to Peru and considered Endangered by the IUCN. It inhabits humid montane forests on the eastern slopes of the Andean cordillera. We collected four faecal samples from different individuals during ecological monitoring. Monitoring was carried out between January and September 2014 in the area known locally as “La Jalca” in the Yambrasbamba community, Amazonas. Samples were collected in May, June, August and September, respectively. Analysis revealed fragments characteristic of the orders Coleoptera, Hymenoptera, Ortoptera and Lepidoptera. Results confirm that small insects form part of the diet of the long whiskered owlet, similar to other small Strigidos.